REPRODUCTIVE HEALTH EDUCATION FOR YOUNG CHILDREN AS A MEASURE TO PREVENT SEXUAL VIOLENCE AT MI 2 ALKHOIRIYAH GARUT - Andhika Lungguh Perceka Andhika Lungguh Perceka; Desy Syswianti Desy Syswianti; Ernawati Ernawati; Taufik Huda Taufik Huda; Aceng Ali Awaludin Aceng Ali Awaludin; Angga Dipa Nagara Angga Dipa Nagara (Jurnal Pengabdian Masyarakat DEDIKASI, 2025)
Sexual violence against children is a serious problem that affects children's physical, psychological, and social development. Young children are highly vulnerable to sexual violence due to their limited knowledge and ability to protect themselves. Therefore, early reproductive health education is an important preventive measure. This community service activity aims to provide reproductive health education to early childhood as an effort to prevent sexual violence at MI 2 Alkhoiriyah Garut. The methods of implementation include the preparation, implementation, and evaluation stages. The preparation stage is carried out through initial observation, coordination with the school, and the preparation of materials tailored to the child's development. The implementation stage was carried out using interactive lectures, educational games, picture stories, and simple simulations. The materials presented included an introduction to body parts, private body parts, gender differences, maintaining personal hygiene, and how to refuse inappropriate touching. Evaluation was carried out through observation and question and answer sessions. The results of the activity showed an increase in children's understanding and awareness of reproductive health and self-protection. Children became more courageous in expressing their opinions and understood the importance of taking care of their bodies. This activity also increased teachers' awareness of the importance of reproductive health education as an effort to prevent sexual violence in schools.